2018
DOI: 10.2139/ssrn.3123226
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Unchained: Rehypothecation Networks, Concentration and Systemic Effects

Abstract: We study how network structure affects the dynamics of collateral in presence of rehypothecation. We build a simple model wherein banks interact via chains of repo contracts and use their proprietary collateral or re-use the collateral obtained by other banks via reverse repos. In this framework, we show that total collateral volume and its velocity are affected by characteristics of the network like the length of rehypothecation chains, the presence or not of chains having a cyclic structure, the direction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…It is hard to underestimate the importance of the presence of bimodular mesoscale structures in real-world networks: while the authors in [26] show that the most robust topology against random failures is the coreperiphery one, understanding the relationship between a given node systemicness and its coreness is of paramount importance in finance [6]. In the same field, a coreperiphery structure is believed to reflect the "essential" function of banks: the core ones tie the periphery ones into a single market through their intermediation activity [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hard to underestimate the importance of the presence of bimodular mesoscale structures in real-world networks: while the authors in [26] show that the most robust topology against random failures is the coreperiphery one, understanding the relationship between a given node systemicness and its coreness is of paramount importance in finance [6]. In the same field, a coreperiphery structure is believed to reflect the "essential" function of banks: the core ones tie the periphery ones into a single market through their intermediation activity [3].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for financial networks, whose structural organization deeply affects their resilience to shocks propagation, node failures, etc. [3][4][5][6]. Several methods have been proposed, so far, to detect communities, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Tout d'abord, elle implique que la politique monétaire doit être attentive à la façon dont les variations des taux d'intérêt à court terme et, par suite, les variations de la courbe des taux affectent la capacité des intermédiaires financiers à emprunter à court terme et à prêter à long terme. Deuxièmement, elle ouvre la voie à un autre canal de transmission de la politique monétaire, que certains appellent le «canal de prise de risque» (Borio et Zhou, 2012, Stiglitz, 2011 (Luu et al 2018). En outre, elles peuvent réduire le risque individuel par la diversification (Allen et Gale 2000, Battiston et al 2012.…”
Section: Reseaux Interconnexions Et Politique Monetaireunclassified
“…De même, si les créanciers décident de thésauriser, cela a des effets externes négatifs sur les liquidités disponibles de leurs emprunteurs. Une cascade de thésaurisation des liquidités peut ainsi se manifester, avec pour conséquence une réduction de la liquidité globale sur les marchés financiers (Gai, Haldane et Kapadia, 2011, Luu et al 2018. D'autre part, il existe des liens indirects entre les banques du fait qu'elles investissent dans des actifs communs (Battiston et al 2012, Cont et al 2013.…”
Section: Reseaux Interconnexions Et Politique Monetaireunclassified
“…Over the last two decades, studies in the broader field of economic and financial networks studies of these systems have shown that the interconnectedness of the economic and financial system is a main driver of (in)stability [3][4][5]. The topology of the networks influences the resilience to shocks [6], and the evolution of mesoscale topological structures could even indicate early-warning signals of a crisis [7].…”
Section: Introductionmentioning
confidence: 99%